2021
DOI: 10.1002/app.51186
|View full text |Cite
|
Sign up to set email alerts
|

Flexible dielectric ZnO‐doped reduced graphene oxide bionanocomposites from solution blending for potential application in bio‐related devices

Abstract: Biocompatible materials with high dielectric constant and low dielectric loss have applications in bio-related electronic devices. Development of flexible materials with those properties is still a challenge. In this work, electrospun membranes and films are prepared from poly(vinyl alcohol) (PVA) and chitosan (CS) solutions, incorporated with a reduced graphene oxide-zinc oxide composite (rGO-ZnO). Blending CS with flexible PVA favors electrospinnability and mechanical properties. ZnO contributes to hinder ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The addition of conducting G‐ZnO and glycerol into PVA‐CS, makes it electroactive, enabling it for effective conduction and distribution of electrical stimulation to the skin tissues at the wound site. An rGO‐ZnO based polymeric composites developed by a Gouvêa et al exhibited conductivities in the range between 8 × 10 −5 S/m and 4 × 10 −4 S/m 25 . Even though GO is more biocompatible, it is weaker in electrical conductivity in comparison to rGO.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The addition of conducting G‐ZnO and glycerol into PVA‐CS, makes it electroactive, enabling it for effective conduction and distribution of electrical stimulation to the skin tissues at the wound site. An rGO‐ZnO based polymeric composites developed by a Gouvêa et al exhibited conductivities in the range between 8 × 10 −5 S/m and 4 × 10 −4 S/m 25 . Even though GO is more biocompatible, it is weaker in electrical conductivity in comparison to rGO.…”
Section: Resultsmentioning
confidence: 99%
“…An rGO-ZnO based polymeric composites developed by a Gouvêa et al exhibited conductivities in the range between 8 Â 10 À5 S/m and 4 Â 10 À4 S/m. 25 Even though GO is more biocompatible, it is weaker in electrical conductivity in comparison to rGO. But, in the present work, the conductivities after the incorporation of G-ZnO were found to be improved and were of the range between 10 À5 and 10 À4 .…”
Section: Studies On Dielectric Parameters and Conductivitymentioning
confidence: 99%
See 2 more Smart Citations
“…The antibacterial activity of gram-positive bacteria was much stronger than that of gram-negative bacteria, and the films had great potential in food packaging. Gouvêa et al reported that reduced graphene oxide (rGO)–ZnO was added to the mixed solution of PVA and chitosan to prepare electrospun membranes and films. Adding rGO-ZnO was helpful in increasing Young’s modulus and stress at break values.…”
Section: Introductionmentioning
confidence: 99%